Cellular self‐organization: An overdrive in Cambrian diversity?. (28th July 2022) - Vujovic, Filip; Hunter, Neil; Farahani, Ramin M.
Abstract: During the early Cambrian period metazoan life forms diverged at an accelerated rate to occupy multiple ecological niches on earth. A variety of explanations have been proposed to address this major evolutionary phenomenon termed the "Cambrian explosion." While most hypotheses address environmental, developmental, and ecological factors that facilitated evolutionary innovations, the biological basis for accelerated emergence of species diversity in the Cambrian period remains largely conjectural. Herein, we posit that morphogenesis by self‐organization enables the uncoupling of genomic mutational landscape from phenotypic diversification. Evidence is provided for a two‐tiered interpretation of genomic changes in metazoan animals wherein mutations not only impact upon function of individual cells, but also alter the self‐organization outcome during developmental morphogenesis. We provide evidence that the morphological impacts of mutations on self‐organization could remain repressed if associated with an unmet negative energetic cost. We posit that accelerated morphological diversification in transition to the Cambrian period has occurred by emergence of dormant (i.e., reserved) morphological novelties whose molecular underpinnings were seeded in the Precambrian period. Abstract : During the early Cambrian period metazoan life forms diverged at an accelerated rate to occupy multiple ecological niches on earth. Evidence is provided that accelerated morphological diversification in transition to the Cambrian period could have occurred by emergence of dormant morphological novelties whose molecular underpinnings were seeded in the Precambrian period.